Super Behaviour: A Note on Young Australian Adults’ Engagement With Their Superannuation Accounts - Malcolm Anderson; Martin Clark; Ian Ramsay; Chander Shekhar (Australasian Accounting, Business and Finance Journal, 2017)
We examine the behaviour and attitudes towards superannuation of 25-34 year old Australians. Our results suggest that they are generally uninterested in their superannuation accounts. They seldom read the information provided by their funds, rarely change their fund, and a majority of them do not make voluntary contributions. Overall the results suggest significant lack of interest in, and engagement and concern with issues related to their retirement planning.
Keywords: Superannuation; young people; fund change; voluntary contribution; behaviour; Australia